2018
DOI: 10.1002/anie.201802309
|View full text |Cite|
|
Sign up to set email alerts
|

Custom‐Made Ceria Nanoparticles Show a Neuroprotective Effect by Modulating Phenotypic Polarization of the Microglia

Abstract: The neuroprotective effect of ceria nanoparticles in the context of brain disorders has been explained by their antioxidant effect. However, the in-depth mechanism remains unknown. As resident immune cells in the brain, microglia exert a variety of functional reprogramming termed as polarization in response to stress stimuli. Herein, custom-made ceria nanoparticles were developed and found to scavenge multiple reactive oxygen species with extremely high efficiency. These nanoparticles drove microglial polariza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
116
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(117 citation statements)
references
References 29 publications
1
116
0
Order By: Relevance
“…b) Schematic illustration for the immunologic effect of CeO 2 nanoparticles. Reproduced with permission . Copyright 2018, Wiley‐VCH.…”
Section: Nanocatalytic Medicine For Nontumoral Therapiesmentioning
confidence: 93%
See 1 more Smart Citation
“…b) Schematic illustration for the immunologic effect of CeO 2 nanoparticles. Reproduced with permission . Copyright 2018, Wiley‐VCH.…”
Section: Nanocatalytic Medicine For Nontumoral Therapiesmentioning
confidence: 93%
“…Recent immunological evidences also indicated that CeO 2 nanoparticles can shift the balance of microglial activation from a proinflammatory M1‐phenotype to an anti‐inflammatory M2‐phenotype by scavenging ROS and blocking the proinflammatory signaling (Figure b), further demonstrating that such an inorganic nanozyme is competent for future clinical brain treatment. In addition to CeO 2 , Fe 3 O 4 nanoparticles, GO quantum dots,141b and melanin nanoparticles (Figure c) have also been applied in nanocatalytic brain disease therapies by ROS depletion in pathological regions.…”
Section: Nanocatalytic Medicine For Nontumoral Therapiesmentioning
confidence: 99%
“…15 Recent studies demonstrating the neuroprotective and cardioprotective roles of CeO 2 nanoparticles have been correlated with its antioxidative and redox-modulatory activities. 16,17 On the other hand, nanoceria have been found to produce significant oxidative stress in human bronchoalveolar carcinoma and 18 human hepatocellular carcinoma. 19 In the case of lung adenocarcinoma (A549) cells, CeO 2 increases the production of ROS which leads to a decrease in the antioxidant level of cells and apoptotic cell death.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Nevertheless, endeavors in developing ceria nanoparticles (NPs) as an effective therapeutic agent have demonstrated the promising potential for the treatment of diseases associated with abrupt surges of ROS. [21][22][23][24][25][26][27] Reversible redox switching between Ce 3+ and Ce 4+ ions in ceria NPs enables the NPs to scavenge ROS for a prolonged period. [28][29][30] Moreover, since it was revealed that Ce 3+ ions are more important than Ce 4+ ions in removing ROS and subsequent amelioration of inflammatory diseases, systems to sustain higher Ce 3+ contents in ceria NPs were designed by inserting dopant ions.…”
Section: Introductionmentioning
confidence: 99%